Eating your way through Luke's gospel - Karris, Robert J. (Collegeville, Minn. : Liturgical Press, 2006)
"Considers the theme of food in Luke's Gospel; links issues of food in Luke with contemporary issues in church and society, as well as with contemporary sociological, cultural, and philosophical analyses of food"--Provided by publisher.
The realia of food and drink during the time of Jesus and Luke -- The theme of food in Luke's Gospel -- Jesus, glutton and drunkard, friend of toll collectors and sinners -- Jesus as guest, host, and teacher at meals -- Jesus' petition for food and food imagery in Luke's parables -- Trawling for the theme of food in the Gospels of John, Mark, and Matthew -- Food and women -- Eating is a serious and dangerous, but also a joyful business.
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Food in the Bible; Dinners and dining in the Bible